Refugees and Asylum Seekers Dispersed in Non-Metropolitan French Cities: Do Housing Opportunities Mean Housing Access? - Gardesse, Camille (2020)
Since 2015, policies for resettling asylum seekers and refugees in European cities have renewed the debate over the governance of migration, while not only metropolises but also small towns and mid-sized cities emerge as, although not new, at least specific arrival spaces. National dispersion policies are assigning these asylum seekers and refugees to small and mid-sized cities that are presumed to provide housing opportunities. However, little is known about access to housing and residential trajectories in these specific urban and socio-economic contexts. This article analyses how the housing providers—either state agencies, managers of temporary accommodation centres or social housing organisations—are adjusting to the arrival and needs of asylum seekers and refugees in cities where there is usually less ethnic diversity. We demonstrate that access to housing and residential trajectories tends to be determined by dispersion and mainstream social mix policies, from national to local arrangements. However, we argue that some pragmatic local practices have reframed this pattern to provide housing solutions that may be contrary to national policies. Our article will be based on 84 in-depth interviews conducted with housing providers, NGOs and with asylum seekers and refugees in three small and mid-sized French cities.